Shikonin Inhibits Der p 2-Induced Cytokine and Chemokine Expression in Dendritic Cells in Patients with Atopic Dermatitis. (2nd August 2020) - Yen, Chung-Yang; Chiang, Wen-Dee; Liu, Shang-Yong; Yu, Sheng-Jie; Hsieh, Ching-Liang
Abstract : Atopic dermatitis (AD) is a common inflammatory skin disorder. Shikonin, the active component of Lithospermum erythrorhizon extract, exhibits anti-inflammatory effects. The objective of the present study was to investigate the effect of shikonin on proinflammatory cytokines and chemokine in patients with AD. Ten patients with AD who were allergic to house dust mite (HDM) and seven healthy controls were recruited in this study. Peripheral blood mononuclear cells were isolated, and CD14 + cells were further selected and differentiated to dendritic cells. Dendritic cells stimulated using Der p 2, the major HDM allergen, were cotreated with shikonin for 24 hours, and dexamethasone was used as a control. Culture supernatants were collected, and proinflammatory cytokine and chemokine concentrations were analyzed using a multiplex assay system. Shikonin significantly inhibited Der p 2-induced expression of interleukin (IL)-6, IL-9, and IL-17A; monocyte chemoattractant protein (MCP)-1; macrophage inflammatory protein (MIP)-1 α ; MIP-1 β ; and Chemokine (C-C motif) ligand 5 (RANTES). The inhibitory effects of shikonin on IL-9, MIP-1 β, and RANTES expression were stronger than those of dexamethasone. Therefore, Shikonin can be considered a promising drug for AD treatment because it inhibits different inflammatory cytokines expression.